State of mental healthcare systems in Eastern Europe: do we really understand what is going on? - Krupchanka, Dzmitry; Winkler, Petr (BJPsych international, 2016)
The article examines the current state of mental healthcare systems in countries of Eastern Europe and derives implications for future research and service development. Analysis of available statistics from the World Health Organization's Mental Health Atlas suggests the need for better-quality data collection. Nonetheless, there appear to be insufficient resources allocated to mental health, lack of involvement of service users in policy-making and, to a large extent, systems continue to rely on mental hospitals. Based on the data presented, a set of directions for future reforms was drafted.